Urinary tract bacterial infection of local Iraqi buffaloes (Bubalus Bubalis) in Mosul city: O. M. Al-Iraqi¹, A. Y. Shareef² and S. H. Dhahir³ - Al-Iraqi, O. M. (The Iraqi Journal of Veterinary Medicine, 2017)
This study is conducted on the samples of urine obtained from buffaloes. Eighty six urine samples were obtained from local buffaloes of different ages, of both sex in Mosul abattoir. The results showed that urine of infected animals was cloudy, dark yellow to reddish color with putrid odor of low specific gravity. Microscopic examination of urine sediment demonstrated increased number of pus cell, erythrocytes, epithelial cell, presence of casts and crystals/ high power filed. Chemical examination revealed elevated urine pH and protein content. Serum examination displayed increase levels of urea and creatinine compered to normal urine samples. Culture of urine samples confirmed 24 positive samples (27.90%). Corynebacterium renale being the most isolated organisms 12(50%), Trueperella pyogens 5(20.83%), Staphylococcus aureus 4(16.66%) and 1(4.16%) for each of Acinetobacter lwoffii, Corynebacterium pilosum and Corynebacterium cystitidis. Male buffalo calves at age 1-3 years revealed high percentage (18.60%) of urinary tract infection, while low percentage of urinary tract infection existed by female buffaloes age more than 3 years (6.98%).